Changes in rectal cancer treatment after the introduction of a national screening program; Increasing use of less invasive strategies within a national cohort. Issue 5 (May 2022) - Giesen, L.J.X.; Olthof, P.B.; Elferink, M.A.G.; van Westreenen, H.L.; Beets, G.L.; Verhoef, C.; Dekker, J.W.T.
Abstract: Aim: Organ preserving treatment strategies and the introduction of a colorectal cancer-screening program have likely influenced the resection rates of rectal cancer. The aim of this study is to assess the influence of these developments on rectal cancer treatment and resection rates in the Netherlands. Methods: Patients diagnosed with non-metastatic rectal cancer between 2013 and 2018, were selected from the Netherlands Cancer Registry. The distribution of surgical and neo-adjuvant treatment and resection rates were analyzed and compared over time. Results: Between 2013 and 2018 22640 patients were diagnosed with non-metastatic rectal cancer. The incidence of early stage (cT1) disease increased from 141 (4%) in 2013 to 448 (12%) in 2018. The use of neoadjuvant radiotherapy and chemo-radiotherapy dropped from 39% to 21% and 34%–25%, respectively. A decrease in surgical resection rates (including TEM) was observed from 85% to 73%. The proportion of patients who underwent endoscopic resections increased from 3% to 10%. The decrease in surgical resection rates was larger in patients treated with neo-adjuvant chemo-radiotherapy. Conclusion: An increase in stage I disease is noted after the introduction of the screening program. Surgical resection rates for rectal cancer have fallen over time. Endoscopic resections due to more early-stage disease probably accounts for a large part of this decline. Furthermore, a watch and wait approach after neo-adjuvant chemo-radiotherapy may play an important role as well.